2022
DOI: 10.1002/alr.22938
|View full text |Cite
|
Sign up to set email alerts
|

Taste receptors in chronic rhinosinusitus, what is the evidence? A systematic review

Abstract: Background Bitter and sweet taste receptors (T2Rs and T1Rs), respectively, are involved in the innate immune response of the sinonasal cavity and associated with chronic rhinosinusitis (CRS). Growing evidence suggests extraoral TRs as relevant biomarkers, but the current understanding is incomplete. This systematic review synthesizes current evidence of extraoral taste receptors in CRS. Methods PubMed, Embase, Cochrane, Web of Science, and Scopus were reviewed in accordance with Preferred Reporting Items for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
(189 reference statements)
1
9
0
Order By: Relevance
“…Recently, a systematic review explored the association of taste receptors with CRS 8 . The review collected 17 studies that had investigated the genotypes of taste receptors and concluded that TAS2R s may have a potential association with CRS, particularly CRSsNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic review explored the association of taste receptors with CRS 8 . The review collected 17 studies that had investigated the genotypes of taste receptors and concluded that TAS2R s may have a potential association with CRS, particularly CRSsNP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review explored the association of taste receptors with CRS. 8 The review collected 17 studies that had investigated the genotypes of taste receptors and concluded that TAS2Rs may have a potential association with CRS, particularly CRSsNP. All 17 of those studies evaluated Western populations, so it was suggested that future investigations involving more diverse institutions and populations be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 29 SNPs in the bitter taste receptor gene TAS2R38 appear to be associated with CRS. 25,26 20 Whole genome sequencing techniques, such as NGS, are becoming more increasingly available and provide a powerful tool to generate "big data," which offer a unique opportunity to gain insights into the mechanisms of complex diseases such as CRSwNP. Proteomics using mass spectrometry and transcriptomics, such as RNA sequencing (RNA-seq), are newer techniques that allow us to gain additional insights and are also becoming more accessible.…”
Section: Snp Genotypingmentioning
confidence: 99%
“…Meanwhile, attempting to elucidate the clinical relevance of extraoral taste receptors in CRS, a systematic review studies with genotypic and phenotypic taste receptor profiles analysis concluded that there is mounting evidence of an association of bitter taste receptors in CRS, particularly in CRSwNP; however, limited evidence and mixed conclusions highlight the need for further study. 43 Finally, Deng et al 44 examined differences in the innervation and the cholinergic receptor patterns in solitary chemosensory cells (SCCs) between inferior turbinate and nasal polyp tissue, and their findings suggested that the lack of trigeminal innervation in nasal polyp tissue may be associated with the SCC proliferation seen in nasal polyps in the setting of type 2 inflammation.…”
Section: Olfaction and Gustationmentioning
confidence: 99%
“…Both studies give further credence to a potential underlying difference in innate immunity that is mediated by bitter and sweet taste receptors in patients with CRS. Meanwhile, attempting to elucidate the clinical relevance of extraoral taste receptors in CRS, a systematic review studies with genotypic and phenotypic taste receptor profiles analysis concluded that there is mounting evidence of an association of bitter taste receptors in CRS, particularly in CRSwNP; however, limited evidence and mixed conclusions highlight the need for further study 43 . Finally, Deng et al 44 .…”
Section: Olfaction and Gustationmentioning
confidence: 99%